REACTIONS KINETICS OF CH3COOH WITH Br2 AS A SIMILIAR ENZYMATIC REACTIONS - Felandi, Novika Tusta; Patiha, Patiha; Pramono, Edi (Alchemy Jurnal Penelitian Kimia, 2013)
The aims of the research are to prove that at certain conditions the reaction between Br2 with CH3COOH is similar to enzymatic reaction, and the value of   calculated from the Espenson equation is different with value calculated by integral method. The experiments were performed at various concentrations of CH3COOH. The reaction studied by spectroscopic method by record the changes in absorbance of Br2 at 400 nm (theabsorbance index is 160 M-1 cm-1) in each definited time range. Data were analyzed with integral equations and the reaction order was determined base on the value of regression coefficient which must be close to 1 or -1. The reaction is said to be similar to the enzymatic reaction if the order of the reaction at initial is different with the order value at the end of reaction. Data were also analyzed using Espenson and integral equation (for comparison). The results showed that at concentrations of CH3COOH 0.00150 M, 0.00100 M, and 0.00075 M and 0.00300 M Br2 the reaction is similar to enzymatic reactions. Meanwhile, at different concentrations of CH3COOH,  the κ value obtained from Espenson equation is different with the value calculated by integral method.